Palynostratigraphy and palaeoclimatic interpretation of the Plio- Pleistocene Lukundol Formation from the Kathmandu valley, Nepal - Bhandari, S.; Paudayal, K. N. (Journal of Nepal Geological Society, 2007)
The Lukundol Formation, a fluvio-lacustrine deposit, constituting the lowermost part of the sedimentary sequence in the Kathmandu valley, is made up of conglomerates in its basal part; thick beds of carbonaceous clay, lignite, silt and sand in the middle part; interbedded clay and gravel in the upper part; and very thick beds of gravel in the uppermost part. Its exposure in the Khahare Khola, near the Lukundol village, is about 205 m thick. The palynostratigraphy of the Lukundol Formation revealed the dominance of gymnosperms over the angiosperms and herbaceous members. In the pollen diagram, Pinus and Quercus are the predominant taxa whereas Castanopsis and Oleaceae are the next dominant ones. Three fossil pollen zones were differentiated in the Lukundol Formation. Zone I indicates a subtropical climate, zone II belongs to a warm temperate climate, and zone III represents a subtropical to warm-temperate climate.